Gênero e empoderamento das advogadas junto às comissões na Ordem dos Advogados do Brasil na região norte - Almeida, Evenise Ribeiro de (Universidade Federal do Tocantins, 2016)
In the survey, we analyze gender relations in the Brazil Lawyers Order-OAB, in Brazil northern region. We seek to understand the changes in this institution, notably with respect to the gender issue, seeking to discuss how OAB has received and reacting to the woman lawyer conquests. We seek to understand how it is being demarcated the possibilities of changes in the gender relations in the composition of Permanent and Special Commissions / Existing Temporaries. Understanding gender that anchors the study is one that deviates from the male power naturalization and approaches of the differences between men and women as a process of social construction. Supported by gender and empowerment categories, research the websites of the OAB and e-SIC-Service Electronic System, we describe about the presence of the woman lawyers in the public and private space, still pointing the professionalization of attorney woman category. By analyzing the number of women lawyers in the conduct of the Order of the Committees in the country northern region, we observe that even with the large number of undergraduate trained women in courses in law and a lot of them entered the Order, they are minorities chairs of the commission, which refers to the difficulty of women in breaking with the male tradition in OAB.